"Śmiechu mi trzeba na te dziwne czasy". Rzecz o Momusie, Apulejuszu, Boccacciu, ośle i stand-upie - Miazek-Męczyńska, Monika (Colloquia Litteraria, 2024)
The article addresses the issue of laughter as a phenomenon that has a cleansing effect on both individuals and entire communities, allowing for the release of negative emotions and escape from fear, doubt and anxiety. The starting point for the considerations are the adventures of Lucius transformed into a donkey from Apuleius’s Metamorphoses, set in the broader context of the ancient view of laughter and sense of humor, as well as modern practices of laughter treatment (gelotherapy).